Monoaminergic Receptors as Modulators of the Perivascular Sympathetic and Sensory CGRPergic Outflows - Marichal-Cancino, Bruno A. (Curr Neuropharmacol, 2020)
Blood pressure is a highly controlled cardiovascular parameter that normally guarantees an adequate blood supply to all body tissues. This parameter is mainly regulated by peripheral vascular resistance and is maintained by local mediators (i.e., autacoids), and by the nervous and endocrine systems. Regarding the nervous system, blood pressure can be modulated at the central level by regulating the autonomic output. However, at peripheral level, there exists a modulation by activation of prejunctional monoaminergic receptors in autonomic- or sensory-perivascular fibers. These modulatory mechanisms on resistance blood vessels exert an effect on the release of neuroactive substances from the autonomic or sensory fibers that modify blood pressure. Certainly, resistance blood vessels are innervated by perivascular: (i) autonomic sympathetic fibers (producing vasoconstriction mainly by noradrenaline release); and (ii) peptidergic sensory fibers [producing vasodilatation mainly by calcitonin gene-related peptide (CGRP) release]. In the last years, by using pithed rats, several monoaminergic mechanisms for controlling both the sympathetic and sensory perivascular outflows have been elucidated. Additionally, several studies have shown the functions of many monoaminergic auto-receptors and hetero-receptors expressed on perivascular fibers that modulate neurotransmitter release. On this basis, the present review: (i) summarizes the modulation of the peripheral vascular tone by adrenergic, serotoninergic, dopaminergic, and histaminergic receptors on perivascular autonomic (sympathetic) and sensory fibers, and (ii) highlights that these monoaminergic receptors are potential therapeutic targets for the development of novel medications to treat cardiovascular diseases (with some of them explored in clinical trials or already in clinical use).